2013
DOI: 10.1099/jmm.0.049072-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the VP4/VP2 coding region in human rhinovirus species C in patients with acute respiratory infection in Japan

Abstract: Detailed genetic analysis was carried out of the VP4/VP2 coding region in human rhinovirus species C (HRV-C) strains detected in patients with acute respiratory infection in Japan. Phylogenetic trees were constructed by the neighbour-joining (NJ) and maximum-likelihood (ML) methods. The NJ phylogenetic tree assigned 11 genotypes to the present strains, whilst the ML tree showed that the strains diversified sometime in the early 1870s. Moreover, the pairwise distance among the present strains was relatively lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The numerous negatively selected sites found in the Kenyan HRV strains may indicate that portion of the genome has attained genetic stability and therefore resist deleterious mutations. These findings echo those of previous reports …”
Section: Discussionmentioning
confidence: 99%
“…The numerous negatively selected sites found in the Kenyan HRV strains may indicate that portion of the genome has attained genetic stability and therefore resist deleterious mutations. These findings echo those of previous reports …”
Section: Discussionmentioning
confidence: 99%
“…HRV-A and -C appear to be mainly associated with ARIs and virus-induced asthma, while HRV-B has been detected in a relatively small number of patients with ARIs (Linsuwanon et al, 2009;Wisdom et al, 2009;Smuts et al, 2011). Our previous findings obtained from samples from children with ARIs in Japan indicated that HRV-A and -C can be classified into many clusters in the phylogenetic tree, with 30% nucleotide divergence of the VP4/VP2 coding region (Mizuta et al, 2010a;Arakawa et al, 2012;Kiyota et al, 2013). In addition, Kiyota et al (2013) estimated that the rate of molecular evolution of the VP4/VP2 coding region was rapid (3.07 × 10 −3 substitutions/site/year) in HRV-C.…”
Section: Molecular Epidemiology Of Hrvmentioning
confidence: 94%
“…Our previous findings obtained from samples from children with ARIs in Japan indicated that HRV-A and -C can be classified into many clusters in the phylogenetic tree, with 30% nucleotide divergence of the VP4/VP2 coding region (Mizuta et al, 2010a;Arakawa et al, 2012;Kiyota et al, 2013). In addition, Kiyota et al (2013) estimated that the rate of molecular evolution of the VP4/VP2 coding region was rapid (3.07 × 10 −3 substitutions/site/year) in HRV-C. These results suggest that HRV-A and -C detected in ARI cases are the predominant strains and have varied genetic properties (Wisdom et al, 2009;Mizuta et al, 2010a;Arakawa et al, 2012).…”
Section: Molecular Epidemiology Of Hrvmentioning
confidence: 99%
“…Few studies have been reported on pathogen profiles, including respiratory viruses, in adult Japanese CAP patients [31]. In addition, the molecular epidemiology of CAPassociated viruses is poorly understood; although, some CAP-associated respiratory viruses such as HMPV and HRV-C have recently been confirmed [32][33][34]. Our results show that HMPV, RSV, HRV, and HPIV are associated with CAP in adult inpatients.…”
Section: Discussionmentioning
confidence: 62%